2019
DOI: 10.1371/journal.pone.0213154
|View full text |Cite
|
Sign up to set email alerts
|

Home care experience and nursing needs of caregivers of children undergoing congenital heart disease operations: A qualitative descriptive study

Abstract: Aims and objectivesTo explore the home care experiences of caregivers taking care of CHD children before and after cardiac surgery.BackgroundDespite the prevalence of congenital heart disease (CHD) in childhood, little is known about the experiences and impacts on the children and their caregivers after CHD diagnosis and surgery. Such knowledge is needed for meaningful support.DesignA qualitative descriptive study.MethodsTwenty-two caregivers of CHD children undergoing cardiac surgery participated in semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 26 publications
(25 reference statements)
2
41
0
15
Order By: Relevance
“…24 Hong Ni et al (2019) showed similar to our review that parents who had a child with CHD, undergo surgery, experienced that they were 'breaking the good life'. 25 In our review, parents also shared that they felt that their view of life changed drastically.…”
Section: Discussionmentioning
confidence: 87%
“…24 Hong Ni et al (2019) showed similar to our review that parents who had a child with CHD, undergo surgery, experienced that they were 'breaking the good life'. 25 In our review, parents also shared that they felt that their view of life changed drastically.…”
Section: Discussionmentioning
confidence: 87%
“…These findings are important given that caregivers of children who underwent cardiac surgery are under great psychological pressure. CHD surgery has a major impact on the financial status of the family, as well as their emotions and well-being [22]. However, it is important to note that caregivers described that being scheduled for surgery induced anxiety but also hope.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers in our study reported that CHD of their child was misdiagnosed multiple times prior to seeking care at a large hospital and patients were waiting for the surgery for more than a year. CHD care in LMICs is not easily accessible for caregivers [15,17,22]. Many visited multiple services and were not able to access surgical services.…”
Section: Discussionmentioning
confidence: 99%
“…Elas são definidas como anomalias estruturais ou funcionais desenvolvidas durante o período embrionário. Algumas malformações nem sempre são aparentes no Recém-Nascido (RN), podendo levar dias, meses ou até anos para se manifestarem (Ni et al, 2019). De etiologia variada, as CCs podem ser desencadeadas por diversos fatores, como: genético, hereditário, ambiental e social (Carlsson, Marttala, Mattsson & Ringnér, 2016a;Carlsson, Bergman, Wadensten & Mattson, 2016b;Queirora et al, 2017;Im et al, 2018).…”
Section: Assistência Multiprofissional E Interdisciplinar Na Abordagem Das Cardiopatias Congênitasunclassified
“…As CCs mais frequentes que podem necessitar de correção cirúrgica são acianóticas, a saber: PCA, CIA, CIV e Desvio do Septo Atrioventricular (DSAV) parcial ou total, cujo predomínio em crianças está relacionado à ocorrência da trissomia 21, conhecida como Síndrome de Dawn (Leite, Mendonça, Cipolotti & Melo, 2012;Ni et al, 2019;Pedra et al, 2019;Saxena et al, 2019).…”
Section: Assistência Multiprofissional E Interdisciplinar Na Abordagem Das Cardiopatias Congênitasunclassified